Removal of 17-α Ethinylestradiol from Water Systems by Adsorption on Polyacrylonitrile Beads: Isotherm and Kinetics Studies - Luigi Mita; Maurizio Forte; Adriana Rossi; Claudia Adamo; Sergio Rossi; Damiano Gustavo Mita; Marco Guida; Marianna Portaccio; Tzonka Godievargova; Ivanov Yavour; Mohamed Samir; Mohy Eldin (Annals of Environmental Science and Toxicology - Peertechz Publications, 2017)
An investigation on the removal of 17-a-Ethinyl Estradiol (EE2) from aqueous solutions using Polyacrylonitrile (PAN) beads has been carried out under closed conditions. The kinetic and equilibrium results obtained for EE sorption with different initial concentrations have been analyzed. Experimental data at equilibrium have been correlated with the Langmuir, Freundlich, Tempkin, and Dubinin-Radushkevich (D-R) isotherm models. The applicability of the isotherm equations to the adsorption system has been compared by means of the correlation coeffi cients. The adsorption data resulted fi tted well by the Freundlich isotherm model. Kinetic analysis was performed with three different types of kinetic adsorption models using the pseudo-fi rst-order, pseudo-second-order, and simple Elovich models. Analysis of the kinetic data indicated that the EE2 adsorption was a second-order process. Diffusion mechanisms have been analyzed by means of the diffusion rate equations inside particulate of Dumwald-Wagner and intraparticle models. The actual rate-controlling step involved in the EE sorption process was determined by further analysis of the sorption data by the kinetic expression given by Boyd. All together these results allowed to understand the adsorption mechanism of the process and have shown the usefulness in using PAN beads in removing EE2 from synthetic aqueous solutions, also at concentrations higher than those measured in the environment.